2021
DOI: 10.1101/2021.07.30.454373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CD49a Identifies Polyfunctional Memory CD8 T cell Subsets that Persist in the Lungs after Influenza Infection

Abstract: CD8 T cell memory offers critical antiviral protection, even in the absence of neutralizing antibodies. The paradigm is that CD8 T cell memory within the lung tissue consists of a mix of circulating TEM cells and non-circulating TRM cells. However, based on our analysis, the heterogeneity within the tissue is much higher, identifying TCM, TEM, TRM, and a multitude of populations which do not perfectly fit these classifications. Further interrogation of the populations shows that TRM cells that express CD49a, b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Several studies have shown that TRM cells are potent cytokine producers [342][343][344]. Expression of CD49a has been linked to enhanced cytokine production of TRM cells in the skin [354] and to a polyfunctional phenotype of lung TRM cells [355]. Our findings that antigen-specific T cells expressing CD49a, CD69 or CD103 in the lung are associated with IFNγ-production supports these previous reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies have shown that TRM cells are potent cytokine producers [342][343][344]. Expression of CD49a has been linked to enhanced cytokine production of TRM cells in the skin [354] and to a polyfunctional phenotype of lung TRM cells [355]. Our findings that antigen-specific T cells expressing CD49a, CD69 or CD103 in the lung are associated with IFNγ-production supports these previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Lung TRM cells cannot be solely identified by expression of (a combination of) CD49a, CD69 and CD103, as some TRM cells have been described to be negative for these markers [355,356]. To distinguish between lung TRM cells and circulating T cells, an intravenous (i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…These findings all correlate with a more "resting" memory phenotype for DP versus the perhaps more "activated" CD49a SP. We have previously reported that the CD49a SP subset has a number of features that correlate with a more effector-like phenotype such as having a higher frequency of Granzyme B and perforin double positive cells, poised for cell killing (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the lungs, T RM are critical for protection against influenza and respiratory syncytial virus, even in the absence of antibodies specific for those viruses (3, 4). T RM have been shown to act as both antigen-specific sentinels linking the innate and adaptive immune systems as well as cytotoxic mediators themselves (5). This functional capacity makes them important players in immunity across multiple organ systems and disease states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation